RANCANGAN APLIKASI PEMBELAJARAN AKSARA JAWA TENTANG MENGOLAH DATA BAGI SISWA MADRASAH IBTIDAIYAH KELAS 1 DAN 2 DI BLITAR JAWA TIMUR - Efendi, Yasin; Effendi, Rustam; Gunawan, Waliadi (Jurnal Ilmiah Sains dan Teknologi, 2021)
Javanese language is one of the lessons that students consider the most boring, especially for students at the level of Madrasah Ibtidaiyah or Elementary Schools. The teaching method of the teacher still uses conventional methods, namely the teacher explains with lectures and students listen to textbooks. The media used are limited to textbooks and white boards. Given the importance of these subjects, a new alternative is needed to support learning media for optimal learning. Although the learning media used currently exist, they are not optimal. So that development needs to be done in order to create more effective learning media. The methodology used is structured analysis and development, starting from analyzing the running system to the proposed system using UML. The final result achieved from this writing is the formation of a system procedure using UML. In addition, an android-based interactive learning media application design using APP Inventor was also produced. The formation of this interactive learning media application design is expected to optimize learning Javanese language subjects about word processing for Madrasah Ibtidaiyah students to support student learning at home and in the classroom.